Pengembangan Media Permainan Monopoli Untuk Meningkatkan Pemahaman Siswa Terhadap Pembelajaran IPAS Materi Wujud Zat dan Perubahannya - Ningsih, Aini Amalia; Juhji, Juhji; Supardi, Supardi (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2025)
This study aimed to develop and evaluate the effectiveness of a Monopoly-based learning media to enhance the understanding of fourth-grade students in Natural and Social Sciences, specifically on the states of matter and their changes. A Research and Development approach was employed using a systematic development model involving curriculum and needs analysis, media design using Canva, expert validation, and small group and field trials. The findings revealed that the developed media was highly effective, with expert validation scores exceeding 85% in feasibility. Students' understanding significantly improved, as reflected in the increase in average test scores from 44.61 (0% mastery) in the pre-test to 76.71 (63% mastery) in the post-test. These results highlight the potential of Monopoly-based learning media as an alternative instructional tool for improving conceptual understanding. Future research is recommended to adapt this media for other subjects and educational levels to explore its effectiveness further.